The Second Crusade and it's Contexts - Rec.: Jonathan Phillips. The Second Crusade. Extending the frontiers of Christendom. New Haven-London: Yale university press, 2007. 364 p. - Marius Ščavinskas (Lietuvos Istorijos Studijos)
-